The Main Reasons, Role and Significance of the US Support for the “Rose Revolution” in Georgia - Chakhoyan, Edgar (YSU Journal of International Affairs, 2022)
This article focuses on the main reasons for the direct and indirect support of the United States during the Rose Revolution in Georgia (2003), its role and significance. Accordingly, the long-term goals of the US financial, advisory, and technical assistance to Georgia after the collapse of the Soviet Union are shown in details. The importance and impact in the political arena of the non-governmental organizations operating in Georgia during the Rose Revolution, especially youth organization “Kmara”, the Open Society Georgia Foundation, the media, Rustavi-2, including the international CNN, exit polls and PVTs have been also focused on.Attention has been paid to the personal connections of the acting and former high-ranking officials of the USA and Shevardnadze, the United States’ dissatisfaction with the regime’s domestic and foreign policy in Georgia, as well as J. Bush Jr.’s tendencies to shape political values ​​through soft power.The opinions of President Shevardnadze, opposition leaders M. Saakashvili, Z. Zhvania, N. Burjanadze, heads of Non-Governmental Organizations, US Ambassador to Tbilisi R. Miles and other experts and officials on the role of the United States in the Rose Revolution are presented in details.The article focuses on the statements of the US officials, the technologies used by the opposition, and the analysis of the political situation in Georgia after the November 2 parliamentary elections.
Keywords: Georgia; Rose Revolution; Open Society; Kmara (It is Enough); “Rustavi-2” TV; Freedom Institute